Comparison of Antiemetic Effects of Ondansetron Granisetron and Tropisetron For Acute Emesis In Ovarian Cancer Patients Receiving Chemotherapy With Paclitaxel and Carboplatin - Taner Turan; Serap Bozok; Nihal Erdoğan; Özlem Karaçay; Gökhan Tulunay; Nurettin Boran; İskender Kög; Faruk Köse (Medical Network, 2007)
OBJECTIVE: Emesis is a critical adverse effect of cancer treatment. In this study, prophylactic activity of ondansetron (OND), tropisetron (TRO) and granisetron (GRA) on acute emesis following carboplatinpaclitaxel chemotherapy was compared. STUDY DESIGN: Charts of 277 patients, who had been treated with first-line carboplatin-paclitaxel combined chemotherapy after being operated with a diagnosis of gynecologic malignancy in between 1993 and 2005, were evaluated retrospectively. After premedication, chemotherapy was initiated with paclitaxel 175 mg/m², infused in three hours. Then, carboplatin was infused in one hour (AUC=6). 90 minutes before the onset of chemotherapy, dexamethasone, 24 mg was infused within an hour. 5 HT3 receptor antagonist (OND=8 mg / TRO=5 mg / GRA=3 mg) were infused for a duration of 30 minutes, one hour before the chemotherapy. Toxicity was evaluated according to WHO criteria. Grade 0 toxicity was accepted as complete response, grade 1 and higher toxicity was accepted unresponsive. RESULTS: The mean age was 55 years. Overall 1582 courses of chemotherapy were given. 241 patients (87%) received six courses. OND was given to 57 (20.6%) patients at 321 (20.3%) courses, TRO to 57 (20.6%) patients at 330 (20.9%) courses and GRA to 163 (58.8%) patients at 931 (58.8%) courses. Grade 3-4 toxicity did not develop in any of the patients. Complete response was achieved in 41.2% of the patients in 77.1% of the cycles. Antiemetic activities of TRO and GRA were stronger than OND. CONCLUSION: Even though this study was retrospective, the treatment and patient groups were homogeneous. Both the discovery of an antiemetic that is much more effective and a protocol that is improved are essential. An emerging need for prospective studies achieved with homogeneous patient groups does exist.